Relationship between oxygen transfer rate and power input in citric acid fermentation by Candida lipolytica - Hassan, M.A. (2014)
A batch culture system for the production of citric acid by Candida lipolytica TISTR 5054 was used to study the relationship between the volumetric oxygen transfer coefficient (kLa) and power requirement in an earated and mixed fermentation system. A 1.2 litre batch stirred tank was used with impeller speeds of 500-900 rpm and aeration rates 0.5-1.0 vvm with 7 percent glucose as the carbon source. The temperature was controlled at 30 degree C. The oxygen transfer coefficient and power consumption were monitored throughout the entire fermentation. The kLa was measured by the dynamic gassing out technique and power was determined using a torque meter fitted to the impeller. The data obtained were fitted to mathematical correlations between kLa, power input during gassing per unit volume of liquid (Pg/V) and superficial gas velocity (U) reported by previous researchers. There were good correlations between the empirical models and the experimental data, characterised by linear regression coefficients R** (2) around 0.8. However, by including the square root of the agitator speed (N), slightly better correlations were obtained (R** (2) of 0.8-0.9), suggesting the importance of stirrer speed in such correlations.